Redes de suporte para crianças com diagnóstico de autismo e suas famílias: um estudo da percepção de pais e cuidadores em diferentes cenários clínicos - Emmanuely Macedo Santana De-Nardin (2020)
OBJECTIVE: This study aimed to know the perception of parents and caregivers of children diagnosed with Autism Spectrum Disorder (ASD) about health care support networks, school and community. METHODOLOGY: This is a study of a primarily qualitative nature of a mixed deductive-inductive approach, conducted through focus groups and subsequent thematic analysis. Four focus groups were conducted with 35 parents and caregivers of children with a confirmed diagnosis of ASD and under 10 years of age, in the municipalities of Belo Horizonte, Contagem and Itabirito, all located in the state of Minas Gerais, Brazil, in scenarios with different clinical characteristics, in public and private health networks. For the conduct of focus groups, a guide-question grid based on initial deductive hypotheses has been used. Focus groups were recorded and fully transcribed for thematic analysis. Clinical and socioeconomic characteristics of parents, caregivers and children were also collected. RESULTS: The parents and caregivers interviewed were, in general, more likely to be women, mother, married, with completed elementary school education up to incomplete higher education. The thematic analysis carried out generated 30 codes distributed in 8 themes of deductive and inductive character (perceptions and feelings of parents and caregivers; social and public policies; support for parents and caregivers; treatment; school; social communication; social interaction; interests and routine). The parents and caregivers interviewed showed, in general, greater dissatisfaction with the support network received, pointing out barriers and difficulties faced in the health, school and community dimensions. Informal support networks, mutual support initiatives, group identification and auto solutions appeared as important coping strategies before social judgments, the father/mother ideal and the ideal of support. Better perceptions and greater satisfaction with support networks appeared more correlated to the offer of guidance emotional support rather than the severity of the clinical manifestations of assisted children and the technical aspects of clinical care, such as the format of the health network being or not as recommended. CONCLUSION: The results of this research point to the importance of the perception of parents and caregivers of children with ASD about support networks as an instrument that can be added to traditional approach techniques to achieve and accommodate the needs of this group. Based on the findings of the parents and caregivers interviewed, early and permanent psychoeducation and emotional support are suggested strategies of exploration and evaluation. The limitations of the study are discussed and the questions about the findings in light of the previous literature are presented in order to provoke clinical developments and directions for a new qualitative and quantitative research in this area.